Mechanical thrombectomy performed in thrombosed fusiform aneurysm after surgery for craniopharyngioma in adult - Ryska, Pavel; Lojik, Miroslav; Kocer, Naci; Zelenak, Kamil; Cesak, Tomas; Cimflova, Petra; Bhorkar, Aprajita Milind; Vitkova, Eva; Krajina, Antonin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2021)
INTRODUCTION: Fusiform dilatation of the internal carotid artery (ICA) is reported as a possible complication of craniopharyngioma resection in childhood. Here, the authors describe such a complication in an adult patient who presented with acute symptomatic thrombosis 7 months after surgery. MATERIALS AND METHODS: A 45-year-old woman presented with left hemispheric stroke due to a thrombotic supraclinoid occlusion of the terminal ICA (so called "T" occlusion). Successful revascularisation was achieved with mechanical thrombectomy. Beside recanalization of the M1 middle cerebral artery segment and ICA, an irregular filling of the fusiform aneurysm of the communicating segment of the left ICA was observed. The patient recovered after mechanical thrombectomy with no clinical sequelae. Due to the persistent filling of the aneurysm sac, a flow diverter stent was deployed across the diseased vessel segment two weeks later. The patient underwent resection of the craniopharyngioma from ipsilateral pterional craniotomy 7 months ago. Five years later the patient works full time as a nurse with no regrowth of the craniopharyngioma and no aneurysm reperfusion. RESULTS: This case, together with four other previously reported cases, documents that fusiform aneurysm as a complication of the craniopharygioma resection is not restricted to the childhood population but may also rarely occur in adults. As the patient suffered from acute symptomatic thrombosis which required treatment under the protocol for acute large vessel occlusions, we decided to treat the aneurysm with the flow diverter stent.
Keywords: acute ischemic stroke; Thrombectomy; Pituitary Neoplasms; výsledek terapie; flow diverter stent; trombóza; Middle Aged; aneurysma; dissecting aneurysm; Adult; Craniopharyngioma; Thrombosis; trombektomie; kraniofaryngeom; nádory hypofýzy; ženské pohlaví; Humans; craniopharyngioma; Aneurysm; stenty; endovaskulární výkony; lidé středního věku; Endovascular Procedures; Stents; endovascular therapy; dospělí; Female; Treatment Outcome; lidé